Epistemological pragmatism of William Kneale as an alternative to strict verificationism - V. V. Ogleznev (Омский научный вестник: Серия "Общество. История. Современность")
This article presents William Kneale’s epistemological pragmatism as an alternative to strict verificationism discussed at the 1945 symposium of the Aristotelian Society. The focus is on his critique of the traditional verificationist criterion of the Vienna Circle and his argument for knowledge as a flexible rather than strictly empirical process. Kneale challenges the view that the meaningfulness of statements is determined by their verifiability and demonstrates that knowledge can exist without explicit hypothesis testing. Unlike Friedrich Waismann, who sought to modernize verificationism, Kneale highlights its limitations. He also disputes Donald MacKinnon’s position, which linked verification to a priori knowledge and the universal subject-predicate structure of language. The analysis of these opposing views shows that the 1945 symposium was a significant milestone in analytic philosophy, anticipating contemporary discussions on meaningfulness, knowledge justification, and the limits of empirical verification.